PENGGUNAAN LABA, ARUS KAS DAN LIKUIDITAS UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS - Ferry Safriandi; Windy Aginta; Wilda Destari Lubis (LP2MTBM MAKARIOZ, 2018)
This study aims to determine the extent to which profit (X1), cash flow (X2) and liquidity (X3) affect financial distress (Y). This research was conducted on LQ45 companies listed on the Stock Exchange with 45 members of the population and obtained 31 samples with the observation year 2015, 2016, 2017 so that 93 samples were obtained using secondary data.This study uses a logistic regression model. To collect data used observation and documentation methods, processing data using SPSS 23.The results showed that earnings (X1) and cash flow (X2) did not affect financial distress (Y), while liquidity (X3) had an effect on financial distress (Y).